Floating young men: Globalization and the crisis of masculinity in Japan - Kumagai, Keichi (Hagar: Studies in Society and Culture, 2013)
This paper highlights a recent change in Japanese men and masculinities in relation to nation and nationalism, as well as the idea of home and domesticity. The prevalence of non-regular employment in the labor market has drastically increased in Japan since the 1990s. This especially hits younger men. as they find it difficult to establish themselves as breadwinners, in keeping with existing gender norms for men. The article examines three types of newly emerging masculinities in Japanese youth: herbivorous boy (soshokukei-danshi), otaku (maniac or fetishist men) and petit (neo) nationalist. Herbivorous boys are tired of hard work and competition and aspire to the comfort of the domestic sphere; they present a mirror image of the corporate warriors of older generations. Otaku place themselves in imaginary homes, either in cyberspace or in commercial "maid-cafés," and are escaping from a commitment to real others. Petit (neo) nationalists turn to Japan as their home and defend it by using an exclusionist discourse that targets neighboring nations and immigrants from foreign countries. In general, as young Japanese men experience growing distress regarding their social stance, it becomes apparent that they are homebound, seeking a sense of domesticity.